Chemical constituents from Lycium barbarum (Solanaceae) and their chemophenetic significance. (August 2021) - Chen, Dongjie; Guo, Sheng; Zhou, Junfei; Zhu, Yue; Zhang, Fang; Zeng, Fei; Duan, Ran; Xu, Mingming; Duan, Jin-ao
Abstract: Phytochemical investigation of the fruit of Lycium barbarum L. has yielded nine alkaloids including one new compound, lycibarbarspermidine T together with eight known compounds. The structures were unambiguously determined by spectroscopic analyses and chemical methods. The chemophenetic significance of all these compounds was summarized. Among the known compounds, compounds 6 and 9 are reported from L. barbarum for the first time, whereas compounds 2 –5 have previously been only found in this plant. The anti-inflammatory effects of all compounds were evaluated by measuring the NO production in RAW 264.7 cells stimulated by lipopolysaccharide (LPS). The results showed that compounds 1 –3 and compounds 5 –9 could inhibit the NO release of RAW 264.7 cells stimulated by LPS at 30 μM. Graphical abstract: Image 1 Highlights: One new spermidine alkaloid, lycibarbarspermidine T (1 ) was isolated from the fruit of Lycium barbarum. Two compounds were isolated from Lycium barbarum for the first time. The chemophenetic significance of all these compounds was discussed. The anti-inflammatory activities of these compounds were reported for the first time.